The current single exhalation method of measuring exhales nitric oxide is affected by airway calibre. - Ho, L; Wood, F; Robson, A; Innes, J; Greening, A (2000)
The authors have observed that some patients with acute exacerbations of asthma do not have substantially higher levels of exhaled nitric oxide (NO). The study examined whether this could be explained by the effect of airway calibre on exhaled NO. Exhaled NO, height and forced expiratory volume in one second (FEV1) were measured in 12 steroid-naive asthmatics and 17 normal subjects. For comparison, another group of patients with airways disease (34 cystic fibrosis patients) were also studied. In 20 asthmatics (on various doses of inhaled steroids, 0-3,200 microg x day-1), exhaled NO was measured before and after histamine challenge (immediately after reaching the provocative concentration causing a 20% fall in FEV1) and in 12 of these patients, also after nebulized salbutamol to restore FEV1 to baseline. Studies were also conducted to examine possible confounding effects of repeated spirometry (as would occur in histamine challenge) and nebulized salbutamol alone in exhaled NO levels. Exhaled NO was measured using a single exhalation method with a chemiluminescence analyser at a constant flow rate and mouth pressure. There was a significant correlation between FEV1 and exhaled NO in steroid naive asthmatics (r=0.9, p<0.001) and cystic fibrosis patients (r=-0.48, p<0.05) but not in normal subjects (r=-0.13, p=0.61). Exhaled NO decreased significantly after histamine challenge and returned to baseline after bronchodilation by nebulized salbutamol (mean+/-SEM: 23.6+/-3.6 parts per billion (ppb) (prehistamine), 18.2+/-2.7 ppb (posthistamine) and 23.6+/-3.8 ppb (postsalbutamol) p=0.001). Repeated spirometry and nebulized salbutamol did not affect exhaled NO measurements significantly. Exhaled nitric oxide levels appear to be lower in circumstances of smaller airway diameter. Hence, within a subject nitric oxide levels may be artefactually decreased during bronchoconstriction. This may be caused by increased airflow velocity in constricted airways when the exhalation rate is kept constant.